GLOBAL HEALTH IN THE GLOBAL NORTH - Black, Steven P., 1980- author. Link (ABINGDON)
1 online resource
Keywords: This book investigates how health interventions are imagined into being in high-income countries, drawing on over seven years of fieldwork in the self-described "global health capital" Atlanta to consider the role of storytelling in the construction of global health futures.The volume highlights the ways in which scientific storytelling is critical to our understanding of how global health futures are constructed. The book examines three value types-epistemic, ethical, and economic-central to contemporary global health and three linguistic and communicative phenomena-multimodal poetics, emplotment, and discursive circulation-significant to the constitution of these values through storytelling. In spotlighting the Atlanta metropolitan region, home to a number of prominent organizations and figures in the development of global health, the book showcases deeper insights into the future-oriented and techno-optimistic stories global health professionals tell each other, funders, and the public. Black builds on these discussions to suggest ways forward for these stories to be improved to foster greater equity and decolonization and re-imagine the future of global health.This book will be of interest to students and scholars in linguistic anthropology, medical anthropology, global health, and health humanities.